PERJANJIAN PENCARTERAN KAPAL TUG BOAT DAN BARGE ANTARA PT. GLOBAL MARINE DENGAN PT. PELAYARAN BUMI - Indriyani; Frilia Esti Anggraeni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2020)
This study aims to determine the implementation of the ship charter agreement, what are the conditions for tugboat and barge charters with a time charter contract, actions for delaying ship returns, and actions for disputes at PT. Global Marine. This study uses a qualitative descriptive research method in the form of written or oral words obtained from observations of the behavior and people associated with the object of this study to obtain secondary data. The results obtained are the process of the occurrence of a ship charter agreement between PT. Global Marine with PT. Pelayaran Bumi is carried out in three (3) main stages, including agreement, chartering agreement, and determination of rental costs. The next research result is the action taken when the ship returns are delayed, namely by applying a bonus ballast, as well as actions when there is a dispute with consensus for consensus, if no consensus is reached, then it can be resolved through the Registrar Office of the Jakarta District Court.